Detection and Extraction of Brain Haemorrhage on The Ct-Scan Image Using Hybrid Thresholding Method - Sumijan (Fakultas Teknik Universitas Bhayangkara, 2016)
Brain bleeding can occur because of the outbreak of the blood vessels in the brain which culminated into haemorrhagic stroke or stroke due to bleeding. Haemorrhagic Stroke occurs when there is a burst of blood vessels result from some trigger factor. Segmentation techniques to Scanner computed tomography images (CT scan of the brain is one of the methods used by the radiologist to detect brain bleeding or congenital abnormalities that occur in the brain.This research will determine the area of the brain bleeding on each image slice CT-scan every patient, to detect and extract brain bleeding, so it can calculate the volume of the brain bleeding. The detection and extraction bleeding area of the brain is based on the hybrid thresholding method.